2022
DOI: 10.1186/s13104-022-06140-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of home-based naturopathic telehealth clinic: an innovative COVID-19 pandemic response

Abstract: Objectives The COVID-19 pandemic in Australia disrupted usual clinical training placements for naturopathic students. An innovative, remote Telehealth clinic was developed and implemented. This pilot study evaluates student and educator learning and teaching experiences in Telehealth. A survey assessed Likert and qualitative written responses to student and staff interaction with the Telehealth clinic. Results Nine student and 12 educator responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Results indicated that value, bene ts, and challenges of telehealth remained consistent with the previous pilot study (17). Respondents perceived continuity of practice, future career success and diversity of patients as important.…”
Section: Value Bene Ts and Challengessupporting
confidence: 76%
See 3 more Smart Citations
“…Results indicated that value, bene ts, and challenges of telehealth remained consistent with the previous pilot study (17). Respondents perceived continuity of practice, future career success and diversity of patients as important.…”
Section: Value Bene Ts and Challengessupporting
confidence: 76%
“…A survey for educators and students, in Additional le 1: Table S1, developed by the research team, was based on previous ndings (17). The current survey examined a range of quality markers for telehealth delivery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Telehealth is technology facilitated healthcare, provided at a distance, that was essential during the COVID-19 pandemic lockdowns for reducing the risk of infection in clinical settings [ 4 , 5 , 7 , 8 ]. CM clinical educators at Torrens University Australia (TUA) implemented telehealth programs that aligned with accrediting body approvals [ 6 , 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%